E-quality Control in Dental Metal Additive Manufacturing Inspection Using 3D Scanning and 3D Measurement - Du, Liang; Lai, Yiwen; Luo, Chunwang; Zhang, Yong; Zheng, Jun; Ge, Xiaohong; Liu, Yuangang (Frontiers in Bioengineering and Biotechnology, 2020)
3D printed metal crowns can be used for dental restorations. The main quality control challenge of these metal dental is the method of quality inspection. Electronic quality is a process by which the quality of the process and the parts produced can be checked online, thereby improving the process and reducing the time it takes for the entire process. Here we propose a combination of 3D scanning and 3D measurement for 3D inspection of metal crowns. The data extracted from the 3D printed metal crowns were used as case studies to prove the proposed method. The obtained results confirm that the new method has very high classification accuracy compared with the traditional inspection methods, and thus yields excellent results.Moreover, the proposed approach is capable to archive 3D models of the parts and achieve rapid quality control. This paper forms the basis for solving many other similar problems that occur in 3D printing related industries.